2004
DOI: 10.1111/j.1349-7006.2004.tb03329.x
|View full text |Cite
|
Sign up to set email alerts
|

Docetaxel enhances the cytotoxicity of cisplatin to gastric cancer cells by modification of intracellular platinum metabolism

Abstract: We have examined the combined anticancer effects of docetaxel (DOC) and cisplatin (CDDP) in vitro using the gastric cancer cell lines MKN-45, MKN-74, and TMK-1. Treatment of the cell lines with 30 µ µ µ µg/ml of DOC for 24 h followed by incubation with 3 or 10 µ µ µ µg/ml of CDDP for 24 h showed a clear synergistic effect. Sequence dependency of the agents was observed in these cell lines: DOC followed by CDDP (DC) showed a stronger antitumor effect than CDDP followed by DOC (CD) in all cell lines. To clarify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 29 publications
3
31
0
Order By: Relevance
“…These transporters mediate drug efflux from tumor cells and may further cause cross-resistance to multiple drugs with diverse chemical structures and curative efficacies. According to previous studies, MDR is observed in the majority of gastric cancers during treatment and is an significant cause of treatment failure (19,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…These transporters mediate drug efflux from tumor cells and may further cause cross-resistance to multiple drugs with diverse chemical structures and curative efficacies. According to previous studies, MDR is observed in the majority of gastric cancers during treatment and is an significant cause of treatment failure (19,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies into the acquisition of CDDP resistance by cancer cells, decreased CDDP accumulation, increased CDDP inactivation, whereas abnormalities in apoptotic signaling have proposed several different mechanisms (14,15). Abnormal expression of the adenosine triphosphate (ATP)-binding cassette (ABC) superfamily of transport proteins, multidrug resistance gene-1 (MDR-1) and multidrug resistanceassociated proteins (MRPs) have been associated with CDDP resistance (16,17). In addition, our previous study showed ABCB1 and CDKN2A gene up-regulation in the CDDPresistant gastric cell line MKN45 (18).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the preclinical synergism between docetaxel and either S-1 or cisplatin [11][12][13][14][15], it was hypothesized that a combination of docetaxel and either S-1 or cisplatin as a secondline treatment might have better efficacy than docetaxel alone, even after the failure of first-line cisplatin plus either S-1 or capecitabine. On the other hand, compared to doc- In contrast, the addition of S-1 to docetaxel showed a better PFS (median, 2.7 months vs. 1.3 months; p=0.034) than docetaxel alone without substantial impairment in the QoL or increasing toxicity except for all grades of nausea.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, docetaxel shows synergistic antitumor activity with fluoropyrimidines, particularly S-1, by modulating the expression of enzymes involved in the 5-FU metabolism, including thymidylate synthase, dihydropyrimidine dehydrogenase, and orotate phosphoribosyltransferase [11,12]. Docetaxel has also shown synergistic activity with cisplatin in gastric cancer, which was attributed partially to the suppression of the cisplatininduced multidrug resistance-associated protein-1 by docetaxel [13], resulting in the accumulation of intracellular platinum-glutathione complexes. Given that these molecules modulated by docetaxel are involved in the resistance to fluoropyrimidines and cisplatin in gastric cancer [14,15], the hypothesis in this study was that the co-treatment of docetaxel and either S-1 or cisplatin could increase the antitumor activity compared to docetaxel alone, by at least partially overcoming the resistance to fluoropyrimidines or cisplatin in patients whose tumors progressed during or after fluoropyrimidines-or cisplatin-based first-line therapy.…”
Section: Introductionmentioning
confidence: 99%